1989
DOI: 10.1111/j.1467-6494.1989.tb00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity and Femininity: A Bipolar Construct and Independent Constructs

Abstract: The present investigation is a reanalysis of data from AntiU and Cunningham (1979, 1980, Marsh, Antill, & Cunningham, 1987 consisting of responses to five masculinity-femimnity (MF) instruments, two self-esteem instruments, and two social desirability scales Correlations between M and F for the five instruments vaned from 23 to approximately -1 0, support for distinguishable (nonbipolar) M and F factors was found for four of the instruments Applying confirmatory factor analysis (CFA) and hierarchical CFA (HCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…This approach is appropriate if: (a) the control variables are theoretically justified; (b) the model complexity is not overstressed; and (c) the sample size is ample (Fletcher et al, 2006). Further, an approach described by Marsh et al (1989) was utilized and resorted items randomly into item parcels, to gain an adequate sample size to parameter ratio. A x 2 /df ratio test, a root mean square error of approximation (RMSEA) index, and a comparative fit index (CFI) were all used to assess the fit of the different models to the data.…”
Section: Analytical Strategymentioning
confidence: 99%
“…This approach is appropriate if: (a) the control variables are theoretically justified; (b) the model complexity is not overstressed; and (c) the sample size is ample (Fletcher et al, 2006). Further, an approach described by Marsh et al (1989) was utilized and resorted items randomly into item parcels, to gain an adequate sample size to parameter ratio. A x 2 /df ratio test, a root mean square error of approximation (RMSEA) index, and a comparative fit index (CFI) were all used to assess the fit of the different models to the data.…”
Section: Analytical Strategymentioning
confidence: 99%
“…For example, in research relating gender roles to self-esteem, Marsh et al (1987Marsh et al ( , 1989 included measures of social desirability in order to control for possible effects of response bias. They concluded that social desirability was an important factor that should be taken into account, and also found that social desirability was consistently related to communion.…”
Section: The Influence Of Social Desirabilitymentioning
confidence: 99%
“…The Bem Sex Role Inventory (BSRI, Bem, 1974). In order to evaluate the instrumental and expressive traits, we chose the BSRI from among other instruments because internationally it is the most extensively used scale (Beere, 1990), despite some conceptual and methodological criticisms (Marsh, Antill, & Cunningham, 1989;Spence, 1991). However, at present, this scale operationalizes the instrumentality/masculinity and expressiveness/femininity traits better than any other.…”
Section: Instrumentsmentioning
confidence: 99%